THEORETIC ANALYSIS OF USING MODELING METHOD IN PSYCHOLOGY - Volzhentseva, Iryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
In the article results of the theoretical analysis of modeling as a method of psychological research and its methods (methods) of scientific cognition are given. The purpose of the study is to theoretically determine the specifics of the use of modeling as a method of psychological research, to develop a general functional scheme for the implementation of modeling procedures in psychology. The theoretical analysis of the main directions of modeling in psychology, the connections of the structure and functions of its complex objects is carried out. It is determined that modeling is a means of creating and researching a model, and a model is an object of scientific knowledge. Using the method of theoretical analysis of domestic and foreign scientific sources, materials on the problem of using modeling in scientific activity have been identified, generalized and systematized. With the help of modern ideological psychological and pedagogical research, the task of determining the principles in the experimental work of scientists has been solved. Results. The main types of models and their essence are schematically presented, the modeling algorithm as a model creation process is identified and characterized. The main directions of modeling in psychology are presented, the general functional system of modeling in psychology is developed, schematically presented and analyzed according to various criteria. It is concluded that modeling is a creative, scientific, purposeful process of constructive - projective, analytical - synthetic activity based on the processing of existing information in order to reflect the object as a whole or its characteristic components; modeling is integrated because it combines theoretical, empirical, developmental and practical aspects and allows deeper insight into the essence of the object research; as a process of education and development of ideas and technologies, as a method of scientific cognition, modeling is multifunctional, multidimensional, multidimensional, as it performs a large number of presented functions of theoretical and empirical research procedures, the use of empirical methods that are aimed at obtaining scientific psychological knowledge and reflect the appearance, structure of the object of research, its behavior, internal or external connections; reveals the systemic organization of the human psyche and many complex objects and psychological neoplasms